2019
DOI: 10.1111/clr.13487
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue response to dental implant closure caps made of either polyetheretherketone (PEEK) or titanium

Abstract: Objective Polyetheretherketone (PEEK) is a popular synthetic thermoplastic polymer for medical applications, but its clinical use suffers from several limitations. Therefore, the aim was to compare the soft tissue response to dental implant closure caps made of PEEK or titanium as evaluated by the occurrence of multinucleated giant cells (MNGCs). Material and methods Forty‐two implants were placed in the maxilla of seven miniature pigs. While commercially pure titanium (Ti) implants had a Ti closure cap, ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…Hahnel et al [44] reported that the oral microflora attached to the PEEK surface was lower than that to zirconia, titanium, and PMMA. Other studies found that the adhesive plaques attached to PEEK healing abutments were reduced compared with titanium abutments, although a similar percentage of adhesive plaques was attached on the two surfaces in vitro studies [45,46]. These findings suggest that high-grade polishing is a key factor in reducing plaque formation.…”
Section: Discussionmentioning
confidence: 77%
“…Hahnel et al [44] reported that the oral microflora attached to the PEEK surface was lower than that to zirconia, titanium, and PMMA. Other studies found that the adhesive plaques attached to PEEK healing abutments were reduced compared with titanium abutments, although a similar percentage of adhesive plaques was attached on the two surfaces in vitro studies [45,46]. These findings suggest that high-grade polishing is a key factor in reducing plaque formation.…”
Section: Discussionmentioning
confidence: 77%
“…Various collagen-based membranes are available for GBR procedures in the fields of oral, and maxillofacial surgery [ 34 ]. Although resorbable collagen-based membranes are favored due to the avoidance of a second surgery, some clinical applications require space maintenance of the barrier membrane with stronger tensile strength or a prolonged biodegradation time [ 35 , 36 , 37 ]. The prolonged barrier functionality is usually achieved by the application of non-resorbable synthetic materials based on titanium or PTFE [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the extraction of suitable, standardized samples for histological analysis is technically challenging and might interfere with the overall implant success. As a result, the majority of controlled studies on soft tissue response to different abutment materials has been performed in a preclinical context (e.g., Caballé‐Serrano et al, 2019; Rea et al, 2017; Welander et al, 2008) or only include clinical parameters, which on their own are limitedly suited as surrogate markers for implant success (van Brakel et al, 2014; Coli & Sennerby, 2019)—particularly at early time points.…”
Section: Introductionmentioning
confidence: 99%